8x+66=-2x-24

Simple and best practice solution for 8x+66=-2x-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+66=-2x-24 equation:



8x+66=-2x-24
We move all terms to the left:
8x+66-(-2x-24)=0
We get rid of parentheses
8x+2x+24+66=0
We add all the numbers together, and all the variables
10x+90=0
We move all terms containing x to the left, all other terms to the right
10x=-90
x=-90/10
x=-9

See similar equations:

| 2x-24=-5x+32 | | 7x+13=-3x+3 | | 1-(y-2)=5+y | | -3x-24=-9x-66 | | -3x+21=2x-24 | | 3x-17=-3x+19 | | 7x+31=-2x-14 | | 10x+74=7x+53 | | (3x-40)=(2x+20) | | 8m+4=4m+12 | | 25+10x-x^=7 | | 3y–12=52+y | | 8x+21=-10x-15 | | -7x-39=-4 | | 3x-15=-5x+9 | | .15y+y=7000 | | 2x+16=5x+28 | | 2(2(x+2)+x)=154 | | 2n+5=3n-10 | | 2(x)+3(x+1)+4(x+2)=56 | | 5/9x=13/6 | | 10x+75=-5x-45 | | 6x-16=-79 | | 4x-32=-3x+31 | | 8x+42=-51 | | -x-9=-10x-27 | | (47)−3×(1649)−1=(47)n−1 | | 3x+10=1x+4 | | 27x-54=-6x^2 | | b/3+7=7 | | (3x+7)=25÷49 | | 9x-3÷5x+5=9÷3 |

Equations solver categories